2016
DOI: 10.1093/abbs/gmw077
|View full text |Cite
|
Sign up to set email alerts
|

miR-378 attenuates muscle regeneration by delaying satellite cell activation and differentiation in mice

Abstract: Skeletal muscle mass and homeostasis during postnatal muscle development and regeneration largely depend on adult muscle stem cells (satellite cells). We recently showed that global overexpression of miR-378 significantly reduced skeletal muscle mass in mice. In the current study, we used miR-378 transgenic (Tg) mice to assess the in vivo functional effects of miR-378 on skeletal muscle growth and regeneration. Cross-sectional analysis of skeletal muscle tissues showed that the number and size of myofibers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…So far, the literature data regarding the function of miR-378 in mSCs are rather inconclusive. Although in vitro studies performed on C2C12 myoblasts demonstrated that miR-378 accelerates differentiation by targeting either musculin, the myogenic differentiation inhibitor (20), or bone morphogenetic protein 4 (BMP4) (59), in vivo experiments on primary mSCs revealed that Tg mice overexpressing miR-378 exhibit delayed muscle regeneration upon acute, cardiotoxin-induced muscle injury by direct targeting insulin-like growth factor 1 receptor (Igf1r) (24). In the current study, the KO of miR-378 in dystrophic animals did not alter the number of mSCs but resulted in a diminished contribution of activated mSCs within the total mSCs, together with decreased proliferation status of mSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the literature data regarding the function of miR-378 in mSCs are rather inconclusive. Although in vitro studies performed on C2C12 myoblasts demonstrated that miR-378 accelerates differentiation by targeting either musculin, the myogenic differentiation inhibitor (20), or bone morphogenetic protein 4 (BMP4) (59), in vivo experiments on primary mSCs revealed that Tg mice overexpressing miR-378 exhibit delayed muscle regeneration upon acute, cardiotoxin-induced muscle injury by direct targeting insulin-like growth factor 1 receptor (Igf1r) (24). In the current study, the KO of miR-378 in dystrophic animals did not alter the number of mSCs but resulted in a diminished contribution of activated mSCs within the total mSCs, together with decreased proliferation status of mSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, it was demonstrated as one of the most upregulated miRNAs in the serum of different mouse models of the disease, as well as in DMD patients, emphasizing its potential utility as a circulating biomarker (22,23). Even more, Zeng et al demonstrated that overexpression of miR-378 attenuated muscle regeneration by delaying mSC activation and differentiation upon cardiotoxin-induced muscle injury (24). Therefore, we sought to explore the role of miR-378 loss in a murine model of DMD, mdx mice, with the special emphasis on pathobiology and severity of the hallmark symptoms of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the overexpression of miR-378 significantly reduced the skeletal muscle mass in mice. Mir-378 attenuated muscle regeneration by delaying the activation and differentiation of satellite cells in mice, especially in sarcopenia [62]. However, there were relatively few studies on target genes for miR-378 to regulate myopenia.…”
Section: Discussionmentioning
confidence: 99%
“…The gene for miR-378 is in the first intron of Pgc-1β and so is expressed more in metabolically active tissue and it has been shown to activate the pyruvate-PEP futile cycle in skeletal muscle of mice whereby it enhances lipolysis in adipose tissue and ameliorates obesity 44 . A further study by the same group showed that miR-378 targets Igfr1 in mice leading to defective muscle regeneration 45 .…”
Section: Discussionmentioning
confidence: 99%